Application of pulsed electric field technology to skin engineering - Berry-Kilgour, C.; Wise, L.; King, J.; Oey, I. (Frontiers in Bioengineering and Biotechnology, 2024)
Tissue engineering encompasses a range of techniques that direct the growth of cells into a living tissue construct for regenerative medicine applications, disease models, drug discovery, and safety testing. These techniques have been implemented to alleviate the clinical burdens of impaired healing of skin, bone, and other tissues. Construct development requires the integration of tissue-specific cells and/or an extracellular matrix-mimicking biomaterial for structural support. Production of such constructs is generally expensive and environmentally costly, thus eco-sustainable approaches should be explored. Pulsed electric field (PEF) technology is a nonthermal physical processing method commonly used in food production and biomedical applications. In this review, the key principles of PEF and the application of PEF technology for skin engineering will be discussed, with an emphasis on how PEF can be applied to skin cells to modify their behaviour, and to biomaterials to assist in their isolation or sterilisation, or to modify their physical properties. The findings indicate that the success of PEF in tissue engineering will be reliant on systematic evaluation of key parameters, such as electric field strength, and their impact on different skin cell and biomaterial types. Linking tangible input parameters to biological responses critical to healing will assist with the development of PEF as a sustainable tool for skin repair and other tissue engineering applications.